1979
DOI: 10.1051/jphyscol:1979385
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Molecules and Liquid Crystals

Abstract: A brief description of the essential features of amphiphillic molecules will be presented. This will be followed by a discussion of specific physical phenomena and their relation to a number of contemporary research areas. Foremost amongst these is the possible application of amphiphillic monolayers to the physics of two-dimensional systems. Specific experimental and theoretical examples will largely be drawn from studies of synthetic phosphatidylcholine (e.g., lecithin) type lipids. Recent experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Separate CP/MAS 13 C NMR experiments 6 have recently shown that the surfactant chain dynamics in silicate−surfactant and binary lyotropic liquid crystals are very similar, and that at room temperature, the silicate−surfactant mesophases are above their Krafft temperatures, consistent with their liquid crystalline properties. These results validate the use of the subscript α (e.g., H α and L α ), which designates the anisotropic liquid-like mobility of the alkyl CTA + chains in silicate−surfactant mesophases.…”
Section: Resultsmentioning
confidence: 96%
“…Separate CP/MAS 13 C NMR experiments 6 have recently shown that the surfactant chain dynamics in silicate−surfactant and binary lyotropic liquid crystals are very similar, and that at room temperature, the silicate−surfactant mesophases are above their Krafft temperatures, consistent with their liquid crystalline properties. These results validate the use of the subscript α (e.g., H α and L α ), which designates the anisotropic liquid-like mobility of the alkyl CTA + chains in silicate−surfactant mesophases.…”
Section: Resultsmentioning
confidence: 96%
“…Diffusive transport of lipids and membrane proteins is of fundamental interest to physics, chemistry, and cell biology, because it typifies two-dimensional diffusion and plays a key role in intracellular signaling . For these reasons, a number of experiments have investigated diffusion in cell and model membrane systems. However, existing ensemble methods that measure the average transport of many lipids (such as fluorescence recovery after photobleaching, FRAP, or electron spin resonance) implicitly rely on assumptions, such as the individual lipid motion is Brownian, , and thus cannot detect complex diffusive behaviors, including subdiffusion.…”
Section: Introductionmentioning
confidence: 99%
“…1 In a pioneering work, Albrecht, Gruler, and Sackmann 6 inferred the occurrence of such a mesophase ͑actually the smectic-C phase differing from the nematic by a finite out-of-plane tilt of molecular long axis͒ in Langmuir monolayers of phospholipids based on indirect evidence from thermodynamic and hydrodynamic behaviors. Although the possibility of 2D smectic-C and/or nematic phases was furthermore supported by numerous statistical theories [7][8][9][10][11][12][13][14][15][16][17][18][19] and computer simulations, [20][21][22][23][24][25] it had taken more than 20 years before this idea was proven to be real through the recent optical microscopic studies of Langmuir monolayers formed by certain thermotropic mesogenic molecules by Adams et al 26 and Tabe and Yokoyama.…”
Section: Introductionmentioning
confidence: 99%